2017
DOI: 10.1007/s00595-017-1531-9
|View full text |Cite
|
Sign up to set email alerts
|

Predictive risk factors for peritoneal recurrence after pancreatic cancer resection and strategies for its prevention

Abstract: Local invasion and tumor size-related factors suggested the possibility of intraoperative dissemination at the time of tumor resection. Preoperative treatment and an operative procedure to prevent tumor exposure may help prevent PR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 28 publications
2
11
0
1
Order By: Relevance
“…The weighted median OS in 13 studies was 19·8 (range 14·0–30·0) months for LR recurrence, 15·0 (10·0–17·7) months for liver recurrence, 30·4 (24·1–40·3) months for lung recurrence and 14·1 (5·5–17·0) months for PeD ( Fig . ).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…The weighted median OS in 13 studies was 19·8 (range 14·0–30·0) months for LR recurrence, 15·0 (10·0–17·7) months for liver recurrence, 30·4 (24·1–40·3) months for lung recurrence and 14·1 (5·5–17·0) months for PeD ( Fig . ).…”
Section: Resultsmentioning
confidence: 98%
“…After removal of 690 duplicates, a further 2588 articles were excluded after title and abstract screening because they did not meet the prespecified inclusion criteria. The full texts of the remaining 468 studies were evaluated in more detail, and 89 studies were found to meet the eligibility criteria for this systematic review. Among them, 22 studies containing information on clinical factors relevant to recurrence sites were selected for the meta‐analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The life expectancy of patients with pleural mesothelioma is often less than 15 months. 41,42 Peritoneal dissemination is frequently caused by recurrent abdominal malignancy in patients with gastrointestinal cancer, 21,22 ovarian cancer, [43][44][45] or pancreatic cancer, [46][47][48] resulting in a poor prognosis for patients. With a great deal of continuous effort to improve the chemotherapeutic regimens, the prognosis of these advanced cancers has currently improved.…”
Section: Discussionmentioning
confidence: 99%
“…However, complete remission does not mean that the cancer cells are absent, but that there is no apparent evidence of cancer. Therefore, since the reemergence of cancer is always possible, a cancer patient after having completed the treatment is required to participate in regular diagnostic procedures The risk of recurrence depends on the cancer type [6][7][8][9].…”
Section: Is It Permanent?mentioning
confidence: 99%